Cricklewood Community Play Association race night - Cricklewood Community Play Association, CCPA (1993)
Typed sheet explaining the 'race night' to be held at Cricklewood Trades Hall on 23 February [year not stated, but probably 1993]. Includes slip for participants who wish to sponsor a race or buy a horse.